Reconciling Rwanda Unity, Nationality and State Control - Melvin, Jennifer (HRC series, 2020)
In July 1994, the Rwandan Patriotic Front (RPF) set out to stabilise and secure Rwanda, a country decimated by genocide. This mandate was later extended to include the herculean task of promoting unity and reconciliation to a population torn apart by violence. More than two decades later, these goals appear to have been achieved. Beneath the veneer of reconciliation lies myriad programmes and legislation that do more than seek to unite the population - they keep the RPF in power. In Reconciling Rwanda: Unity, Nationality and State Control, Jennifer Melvin analyses the highly controversial RPF and its vision of reconciliation to determine who truly benefits from the construction of the new post-genocide Rwanda.